2021
DOI: 10.3390/ijms22105104
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Wound Healing, Fibrosis, and Cancer: The Paradigm of Recessive Dystrophic Epidermolysis Bullosa

Abstract: Recessive Dystrophic Epidermolysis Bullosa (RDEB) is a devastating skin blistering disease caused by mutations in the gene encoding type VII collagen (C7), leading to epidermal fragility, trauma-induced blistering, and long term, hard-to-heal wounds. Fibrosis develops rapidly in RDEB skin and contributes to both chronic wounds, which emerge after cycles of repetitive wound and scar formation, and squamous cell carcinoma—the single biggest cause of death in this patient group. The molecular pathways disrupted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 109 publications
(146 reference statements)
0
16
0
2
Order By: Relevance
“…The clinical phenotypes of our five DEB cases were consistent with this pattern; thus, Cases 1, 3 and 6 showed more severe and widespread symptoms. However, it was also observed that the brothers in Case 3 showed some difference in phenotypic severity, which suggests that there may be other factors regulating DEB phenotypes, which need further clarification ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical phenotypes of our five DEB cases were consistent with this pattern; thus, Cases 1, 3 and 6 showed more severe and widespread symptoms. However, it was also observed that the brothers in Case 3 showed some difference in phenotypic severity, which suggests that there may be other factors regulating DEB phenotypes, which need further clarification ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unbalance of the sequential and partly overlapping four wound healing phaseshemostasis, inflammation, cell proliferation, and tissue remodeling-may result in two opposite detrimental outcomes: a delay or lack of wound closure and the formation of a hypertrophic scar (Gurtner et al 2008). Multiple factors, insisting mainly on the last three phases of wound healing, variedly undermine wound healing and repair processes and underpin both chronic wounds and fibrosis observed especially in severe EB forms (Pfendner and Lucky 1993;Fine et al 2014;Cianfarani et al 2017;Tartaglia et al 2021). Skin fragility and recurrent blisters cause persistent inflammation, delayed reepithelization, and nonhealing ulcers, which become easily infected, further protracting the healing pro-cess (Cianfarani et al 2017;Tartaglia et al 2021).…”
Section: Wound Healing In Ebmentioning
confidence: 99%
“…Multiple factors, insisting mainly on the last three phases of wound healing, variedly undermine wound healing and repair processes and underpin both chronic wounds and fibrosis observed especially in severe EB forms (Pfendner and Lucky 1993;Fine et al 2014;Cianfarani et al 2017;Tartaglia et al 2021). Skin fragility and recurrent blisters cause persistent inflammation, delayed reepithelization, and nonhealing ulcers, which become easily infected, further protracting the healing pro-cess (Cianfarani et al 2017;Tartaglia et al 2021). Unresolved microbial infection drives persistent wound inflammation via innate and adaptive immune activation (Dovi et al 2003;Mori et al 2004;Goren et al 2009;Tanno et al 2017;Fuentes et al 2020).…”
Section: Wound Healing In Ebmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural and functional interdependence of both major networks is reflected by common clinical features of patients with deficiencies in collagen or elastic fiber network components, that are often accompanied by similar dysregulated signaling pathways. For instance, aberrant TGF-β and integrin signaling have been shown to be involved in several types of osteogenesis imperfecta (OI) ( Grafe et al, 2014 ; Etich et al, 2020 ) epidermolysis bullosa (EB) ( Kiritsi and Nystrom, 2018 ; Tartaglia et al, 2021 ), Ehlers-Danlos (EDS) ( Morissette et al, 2014 ), cutis laxa (CL) ( Urban and Davis, 2014 ), and in the fibrillinopathies ( Sengle and Sakai, 2015 ).…”
mentioning
confidence: 99%